2007
DOI: 10.1080/03009740601089648
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Ser413/Ser ofPAI‐2 polymorphism Ser413/Cys is associated with anti‐phospholipid syndrome and systemic lupus erythematosus in a familial case: comparison with healthy controls

Abstract: Our data indicate that this family did not follow the Mendelian inheritance pattern. The Ser(413)/Ser genotype demonstrated in 60% of the affected members (3/5) of this family might increase the risk for autoimmune syndromes such as APS or SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…These analyses support efforts to understand the regulatory dynamic of SERPINB2 . It is the most highly upregulated gene in inflammatory bowel disease, strongly upregulated in SLE, and sequence variants are associated with multiple human diseases [1, 2, 40, 41]. Our lack of understanding of the regulatory landscape is a significant knowledge gap.…”
Section: 0 Resultsmentioning
confidence: 99%
“…These analyses support efforts to understand the regulatory dynamic of SERPINB2 . It is the most highly upregulated gene in inflammatory bowel disease, strongly upregulated in SLE, and sequence variants are associated with multiple human diseases [1, 2, 40, 41]. Our lack of understanding of the regulatory landscape is a significant knowledge gap.…”
Section: 0 Resultsmentioning
confidence: 99%
“…Although the functional consequences of these residue changes are unknown, several studies have linked PAI-2 genotype and disease. Form A has been associated with lupus erythematosus and thrombic pneumonia in patients with this condition, 117 antiphospholipid syndrome 118 and myocardial infarction, 119,120 although Foy and Grant 121 found no evidence of the link between PAI-2 variants and myocardial infarction. These disease states all relate to disorders in hemostasis, highlighting the role of PAI-2 in this system.…”
Section: Post-transcriptional Controlmentioning
confidence: 98%
“…Candidate gene association studies and gene expression profiling have identified APS susceptibility genes involved in coagulation, inflammation and innate immune response [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, and despite some experimental evidences connecting atherosclerosis and aPLA, none of these studies have focused their attention on genes related to atherosclerosis in aPLA carriers.…”
Section: Introductionmentioning
confidence: 99%